THE MARITAL STATUS AND PSYCHOSOMATIC STATUS, AS RISK'S FACTORS OR ANTIRISK'S FACTORS OF OPIOID DEPENDENCE'S FORMATION - Druz', O.V. (World of Medicine and Biology, 2010)
Comparative research of frequency of different kinds of the marital status, the mental status and belonging to the certain constitutional and morphological types, in the elected groups was carried out. It is established that among all investigated risk factors of formation of dependence from opioids the most powerful are asthenic constitutional and morphological type with a circle of chest
Keywords: opioid' dependence; risk factors; marital status and psychosomatic status